Efek Pra-perlakuan Resin Komposit dan Semen Ionomer Kaca Terhadap Kebocoran Tepi - Alfonsius Ega Marvin; Octarina Octarina (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Application material pit and fissure sealants on teeth especially with deep pits and fissures as caries prevention. Material for pit and fissure sealants generally using resin composite and glass ionomer cement. The materials have differences of composition, technique, and application. Over time, material pit and fissure sealants on teeth often found not intact. To determine microleakage of the pit and fissure sealants which cause restoration failure. A total of 60 extracted human upper premolars teeth divided into 4 groups, i.e. flowable composite without etching (group A), flowable composite with etching (group B), glass ionomer cement without dentin conditioner (group C), and glass ionomer cement with dentin conditioner (group D). Each group divided into 3 subgroups, i.e. immersed in artificial saliva for 0, 7, and 14 days, 37 ̊C. After that, immersed in Methylene Blue 1% for 48 hours. Each specimen was sectioned using Struers Accutom-2 and examined using Stereomicroscope (Nikon, Japan) to determine the extent of dye penetration. Existing data was tested using statistical SPSS 17 Kolmogorov-smirnov. Group A and B have minimal microleakage than group C and D (p<0.05). Group B has minimal microleakage than group A (p>0.05). Pre-treatment etching before application composite flowable may increase the adhesion. Meanwhile, pre-treatment dentin conditioner before application glass ionomer cement didn’t affect the adhesion.